KONSEP PEMIKIRAN PENDIDIKAN ISLAM PERSPEKTIF AL-GHAZALI - Rifdatul Maula (Jurnal Ilmu Pendidikan Islam, 2021)
Abstract In this study, the author will explore the concept of education of al-Ghazali which he is a famous Muslim scholar both among the Islamic world and among the western world. He is also one of the most famous Muslim philosophers in the field of education. Al-Ghazali not only as a philosopher, but also as a teacher and the enforcers of truth when the decadence of morality and religion of his time. The thought of the concept of Islamic education of al-Ghazali when viewed from the way grouping, looks like a separate thought with each other, but organically the grouping is the subjects that are interconnected. The contribution he gave in the field of Islamic education is through a number of essays he composed like the science of fiqh, tasawwuf, adab, and other sciences from the results of his thinkers. The contribution has been able to deliver to the benefit of the people who depth, and can be used as a reference for the next generation. So, should the knowledge of the concept of Islamic education in the perspective of al-Ghazali need to be studied more deeply for both educators and learners, in order to take more benefit from the concept of Islamic education initiated by him. Keywords: Concept, Islamic Education, Al-Ghazali Abstrak Pada kajian ini, penulis akan mengupas tentang konsep pendidikan islam perspektif al-Ghazali yang mana beliau adalah seorang ilmuwan muslim terkenal baik dikalangan dunia islam maupun dikalangan dunia barat. Beliau juga adalah salah satu dari filosuf muslim terkenal yang berkiprah dalam bidang pendidikan. Bukan hanya sebagai filosuf, al-Ghazali juga sebagai seorang guru serta penegak kebenaran ketika terjadi dekadensi moral dan agama pada masanya. Pemikiran konsep pendidikan islam al- Ghazali jika ditinjau dari cara pengelompokannya, tampak seperti pemikiran yang terpisah anata satu dengan yang lainnya, akan tetapi secara organik pengelompokan tersebut merupakan subyek-subyek yang saling berhubungan. Adapun Kontribusi yang beliau berikan dalam bidang pendidikan islam adalah melalui sejumlah karangan-karangan yang beliau susun seperti ilmu fiqh, tasawwuf, adab, dan ilmu- ilmu lain dari buah hasil pemikiranya. Kontribusi tersebut telah dapat menghantarkan kepada kemanfaatan bagi orang-orang yang mendalaminya, serta dapat digunakan sebagai rujukan bagi generasi sesudahnya. Sehingga seyogianya pengetahuan tentang konsep pendidikan islam perspektif al-Ghazali perlu dikaji lebih mendalam lagi baik bagi para pendidik maupun peserta didik, agar dapat mengambil lebih banyak manfaaat dari konsep pendidikan islam yang digagas oleh beliau. Kata kunci: Konsep, Pendidikan Islam, Al-Ghazali